Identification of a novel pyridine derivative with inhibitory activity against ovarian cancer progression in vivo and in vitro - Si, Lulu; Lai, Tianjiao; Zhao, Junru; Jin, Yuxi; Qi, Meng; Li, Mingyue; Fu, Hanlin; Shi, Xiaojing; Ma, Liying; Guo, Ruixia (Frontiers in Pharmacology, 2022)
Ovarian cancer is the second leader killer of female gynecological malignant tumors patients worldwide. Although surgery and chemotherapy have achieved dramatic achievement, the mortality remains high, resulting into the demand of new specific drug discovery. Disrupting ovarian cancer growth via histone deacetylases (HDACs) inhibition is a strategy for cancer therapy or prevention. In this work, we synthesised a novel pyridine derivative named compound H42 and investigated its anticancer activities in vivo and in vitro. We found that compound H42 inhibited ovarian cancer cells proliferation with IC50 value of 0.87 μM (SKOV3) and 5.4 μM (A2780) respectively. Further studies confirmed that compound H42 induced apoptosis, intracellular ROS production and DNA damage. Moreover, compound H42 downregulated the expression of histone deacetylase 6 (HDAC6) with a distinct increasing in the acetylation of α-tubulin and Hsp90, followed by the degradation of cyclin D1, resulting into cells cycle arrest at the G0/G1 phase. Importantly, ectopic expression of HDAC6 induced deacetylation of (heat shock protein) Hsp90 and cyclin D1 up-regulation. However, in the nude xenograft mice study, compound H42 treatment can inhibit ovarian cancer growth without obvious toxicity. These finding indicated that compound H42 inhibited ovarian cancer cells proliferation through inducing cells cycle arrest at G0/G1 phase via regulating HDAC6-mediated acetylation, suggesting compound H42 could serve as a lead compound for further development of ovarian cancer therapeutic agent.